PERFORMANCE ANALYSIS OF THEACHER WHO HAVE MULTIPLE ROLES IN GMIM BUHA ELEMENTARY SCHOOL, MANADO CITY - Angelin Togelang; Angelin Togelang (PT. Giat Konseling Nusantara, 2025)
The purposeofthis study istoobtain a description and results of data analysis on the condition of teacher performance Christian Religious Education at SD GMIM Buha. The impact of dual roles on teacher performance at SD GMIM Buha Efforts to overcome performance barriers for teachers who have multiple roles at SD GMIM Buha. To achieve the research objectives, the research used qualitative research methods using descriptive approach techniques and incollecting data by observation, interviews and study of documents then the data obtained was analyzed through analytical procedures with several stages, namely data collection, data reduction, presentation data and conclusion/verification. Based on the results of there search, the conclusions are (1) teacher performance is still low, seen from the presence and activeess of teachers in learning and activities at school (2) the dual roleof a teacher is the reason for not being able to carry out responsibilities at school (3) efforts which is carried out from the school leadership of more stringent coaching, monitoring and assessment and to teachers who have a more professional double role in increasing capacity as Christian Religious Education teachers.